Antimicrobial Activity Test of Bitter Melon (Momordica charantia L.) Plant Extract Against Staphylococcus epidermidis, Escherichia coli Bacteria and Candida albicans - Dewa Ayu Citra Rasmi; Lalu Zulkifli; Nurul Ahadia (Jurnal Penelitian Pendidikan IPA, 2023)
Bitter gourd (Momordica charantia L.) contains secondary metabolites of flavonoids, alkaloids, saponins, and steroids that act as antimicrobials. This study aimed to determine the antimicrobial activity of bitter melon (Momordica charantia L.) plant extract in N-hexane and ethanol solvents against Staphylococcus epidermidis, Escherichia coli, and Candida albicans. This research is an experimental laboratory study, namely the antimicrobial activity test of bitter melon plant extract on the growth of test bacteria using the agar diffusion method. The study's experimental design used a Completely Randomized Design with three repetitions at three concentration variations, namely 30%, 45%, and 60%. Then phytochemical screening was carried out to determine the active compounds in the bitter melon plant extract. Data on the inhibitory power of bitter melon plant extract were analyzed qualitatively, and the differences between concentrations were seen using the ANOVA (Analysis of variance) test. The results showed that bitter melon (Momordica charantia L.) plant extract in ethanol solvent showed activity against the growth of Staphylococcus epidermidis, Escherichia coli bacteria with a concentration of 60%, producing a powerful inhibition zone.